Catalytic and engineering strategies for enhanced hydrogenation reactions: A review of heterogeneous catalysts and process optimization - Yihui Song; Shuhao Liu; Peiliang Sun; Weibin Qiu; Yibao Li; Chong Peng (Results in Engineering)
Hydrogenation technology is an essential cornerstone in the production of clean oils and the improvement of product quality, which is the core of refining and chemical integration. Despite its extensive development over decades, considerable strides have been made in hydrogenation technology, but there are still several problems such as high investment and operating costs, alongside elevated energy consumption, etc., which are unable to meet the requirements of petrochemical companies for sustainable development. Herein, this review endeavors to systematically discuss the principle of intensified hydrogenation process via catalytic chemistry and engineering, which involved catalytic materials and the process design, etc. Deeply acknowledge that optimizing catalyst design and upgrading process equipment effectively enhance hydrotreating efficiency. Furthermore, the perspectives for hydrotreating and hydrocracking technologies are explored, with a focus on pivotal research directions such as biomass conversion technology and the upgrading and utilization of waste plastics.